Clinical usefulness of a deep learning‐based system as the first screening on small‐bowel capsule endoscopy reading. Issue 4 (2nd October 2019) - Aoki, Tomonori; Yamada, Atsuo; Aoyama, Kazuharu; Saito, Hiroaki; Fujisawa, Gota; Odawara, Nariaki; Kondo, Ryo; Tsuboi, Akiyoshi; Ishibashi, Rei; Nakada, Ayako; Niikura, Ryota; Fujishiro, Mitsuhiro; et al.
Abstract : Background and Aim: To examine whether our convolutional neural network (CNN) system based on deep learning can reduce the reading time of endoscopists without oversight of abnormalities in the capsule‐endoscopy reading process. Methods: Twenty videos of the entire small‐bowel capsule endoscopy procedure were prepared, each of which included 0–5 lesions of small‐bowel mucosal breaks (erosions or ulcerations). At another institute, two reading processes were compared: (A) endoscopist‐alone readings and (B) endoscopist readings after the first screening by the proposed CNN. In process B, endoscopists read only images detected by CNN. Two experts and four trainees independently read 20 videos each (10 for process A and 10 for process B). Outcomes were reading time and detection rate of mucosal breaks by endoscopists. Gold standard was findings at the original institute by two experts. Results: Mean reading time of small‐bowel sections by endoscopists was significantly shorter during process B (expert, 3.1 min; trainee, 5.2 min) compared to process A (expert, 12.2 min; trainee, 20.7 min) ( P < 0.001). For 37 mucosal breaks, detection rate by endoscopists did not significantly decrease in process B (expert, 87%; trainee, 55%) compared to process A (expert, 84%; trainee, 47%). Experts detected all eight large lesions (>5 mm), but trainees could not, even when supported by the CNN. Conclusions: Our CNN‐based system for capsule endoscopy videos reduced the reading time of endoscopists without decreasing the detection rate of mucosal breaks. However, the reading level of endoscopists should be considered when using the system.